Characterisation of bituminite and testing reproducibility of vitrinite and bituminite reflectance measurements in organic‑carbon-rich intervals of the Kimmeridge Clay Formation: ICCP Identification of Dispersed Organic Matter Working Group round robin exercises - J. Kus; A.G. Borrego; B. Bielowicz; P. Crosdale; M.-E. Damoulianou; D. Flores; C. Fonseca; P.A. Gonçalves; P.C. Hackley; M. Hámor-Vidó; S. Henne; B. Holstein; et al. (International Journal of Coal Geology, 2026)

Artificial intelligence in sustainable organic waste treatment: a review - Dharshika Sugumaran; Madushan D. Udakandage; Sanduni P. Kodippili; Maleesha M. De Alwis; Danushika L. Attigala; Neeliya N. Ranasinghe; Danushika C. Manatunga; Rohan S. Dassanayake; Yang Zhou; Yuanyuan Liu (Waste Disposal & Sustainable Energy, 2025)

Optimizing intercropping selection for coconut plantations based on PAR and agro-climatic zones - S. S. Udumann; C. S. Ranasinghe; L. K. N. G. Karunarathna; P. E. Kaliyadasa; T. D. Nuwarapaksha; U. G. A. T. Premathilaka; Anjana J. Atapattu (Agroforestry Systems, 2024)

Resource potential of the Proterozoic–Paleozoic Carrara depocentre, South Nicholson region, Australia: Insights from stratigraphic drilling - E. Grosjean; A.J.M. Jarrett; C.J. Boreham; L. Wang; L. Johnson; J.M. Hope; P. Ranasinghe; J.J. Brocks; A.H.E. Bailey; G.A. Butcher; C.J. Carson (Organic Geochemistry, 2023)

Conversion of energy and protein rich food waste as an alternative feed ingredient in broiler feed formulation - R. A. U. J. Marapana; W. M. P. B. Weerasinghe; G. S. A. Senanayake; P. R. D. Perera; T. R. Seresinhe; R. A. S. N. Ranasinghe; R. A. A. P. Marapana (Tropical Animal Health and Production, 2023)

Nutritional Value and Potential Applications of Jellyfish - R. A. S. N. Ranasinghe; W. L. I. Wijesekara; P. R. D. Perera; S. A. Senanayake; M. M. Pathmalal; R. A. U. J. Marapana (Journal of Aquatic Food Product Technology, 2022)

Physiological, biochemical and molecular evaluation of micropropagated and seed-grown coconut (Cocos nucifera L.) palms - H. D. D. Bandupriya; S. A. C. N. Perera; C. S. Ranasinghe; C. Yalegama; H. P. D. T. Hewapathirana (Trees, 2022)

Kidney Cadmium Concentrations in an Urban Sri Lankan Population: an Autopsy Study - S. A. Gunawardena; M. Ranasinghe; T. Ranchamali; P. Dileka; J. W. Gunawardana (Biological Trace Element Research, 2021)

Correction to: Schistosomiasis—from immunopathology to vaccines - Donald P. McManus; Robert Bergquist; Pengfei Cai; Shiwanthi Ranasinghe; Biniam Mathewos Tebeje; Hong You (Seminars in Immunopathology, 2020)

Schistosomiasis—from immunopathology to vaccines - Donald P. McManus; Robert Bergquist; Pengfei Cai; Shiwanthi Ranasinghe; Biniam Mathewos Tebeje; Hong You (Seminars in Immunopathology, 2020)

Morphodynamic Acceleration Techniques for Multi-Timescale Predictions of Complex Sandy Interventions - Arjen P. Luijendijk; Matthieu A. de Schipper; Roshanka Ranasinghe (Journal of Marine Science and Engineering, 2019)
Thirty one percent (31%) of the world’s coastline consists of sandy beaches and dunes that form a natural defense protecting the hinterland from flooding. A common measure to mitigate erosion along sandy beaches is the implementation of sand nourishments. The design and acceptance of such a mitigating measure require information on the expected evolution at time scales from storms to decades. Process-based morphodynamic models are increasingly applied, together with morphodynamic acceleration techniques, to obtain detailed information on this wide scale of ranges. This study shows that techniques for the acceleration of the morphological evolution can have a significant impact on the simulated evolution and dispersion of sandy interventions. A calibrated Delft3D model of the Sand Engine mega-nourishment is applied to compare different acceleration techniques, focusing on accuracy and computational times. Results show that acceleration techniques using representative (schematized) wave conditions are not capable of accurately reproducing the morphological response in the first two years. The best reproduction of the morphological behavior of the first five years is obtained by the brute force simulations. Applying input filtering and a compression factor provides similar accuracy yet with a factor five gain in computational cost. An attractive method for the medium to long time scales, which further reduces computational costs, is a method that uses representative wave conditions based on gross longshore transports, while showing similar results as the benchmark simulation. Erosional behavior is captured well in all considered techniques with variations in volumes of about 1 million m 3 after three decades. The spatio-temporal variability of the predicted alongshore and cross-shore distribution of the morphological evolution however have a strong dependency on the selected acceleration technique. A new technique, called ’brute force merged’, which incorporates the full variability of the wave climate, provides the optimal combination of phenomenological accuracy and computational efficiency (a factor of 20 faster than the benchmark brute force technique) at both the short and medium to long time scales. This approach, which combines realistic time series and the mormerge technique, provides an attractive and flexible method to efficiently predict the evolution of complex sandy interventions at time scales from hours to decades.

Risk-Averse Economic Optimization in the Adaptation of River Dikes to Climate Change - L. Wang; P. H. A. J. M. van Gelder; J. K. Vrijling; S. Maskey; R. Ranasinghe (Water Resources Management, 2015)

The morphological response of large tidal inlet/basin systems to relative sea level rise - D. M. P. K. Dissanayake; R. Ranasinghe; J. A. Roelvink (Climatic Change, 2012)